Activity, abundance and community structure of anammox bacteria along depth profiles in three different paddy soils. (December 2015) - Bai, Ren; Xi, Dan; He, Ji-Zheng; Hu, Hang-Wei; Fang, Yun-Ting; Zhang, Li-Mei
Abstract: Anaerobic ammonium oxidation (anammox) is a globally important nitrogen-cycling process mediated by specialized microbes, and has been demonstrated to be ubiquitous in anoxic natural settings and bioreactors. However, our knowledge of its prevalence in different paddy soil types and along the depth profiles remains largely undocumented. Here, mesocosm incubations were constructed to investigate the activity and community compositions of anammox bacteria across different depth layers of three different paddy soils. 15 N tracer experiments showed that anammox rates were prevalent in almost all depth layers of an inceptisol (Binhai, BH) and an oxisol (Leizhou, LZ), but was absent in an ultisol (Taoyuan, TY). The functional gene hzsB of anammox bacteria was only detected in BH and LZ soil profiles with detected anammox activity. Anammox accounted for 0.4%–12.2% of the total N2 production, and anammox rates were 0.02–0.77 nmol N g −1 dry soil h −1 and significantly correlated with soil pH and electric conductivity. Anammox activity and abundance of hzsB genes were significantly lower in the surface soil layers (0–5 cm) than in the sub-surface soil layers (20–60 cm). Candidatus Brocadia, Candidatus Kuenenia and Candidatus Jettenia were detected by cloning and sequencing, with Candidatus Brocadia being dominant in all the three soils and Candidatus Jettenia being more frequently detected in the LZ soil. The operational taxonomic unit number and diversity indices of anammox bacterial 16S rRNA gene increased with soil depth. Our results demonstrate that anammox is more common and active in alkaline soils than in acidic soils, in deep paddy soil layers than in surface soil layers, and that anammox activities are likely to be regulated by soil chemical properties such as pH, salinity and redox potential. Highlights: Anammox was more common and active in alkaline than in acidic paddy soils. Anammox was relatively low or absent in surface but was active in sub paddy soils. Anammox bacterial community structure was distinct in three paddy soils.